1991
DOI: 10.1084/jem.174.3.741
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-mediated dissolution of infected host cells as a defense strategy against a facultative intracellular bacterium.

Abstract: The rate of growth of Listeria monocytogenes in the livers of mice infected intravenously with a lethal or sublethal inoculum of this facultative intracellular bacterium is greatly increased if neutrophils and other host cells are prevented from accumulating at foci of infection during the first 24 h by treatment with a monoclonal antibody (5C6) specific for the type 3 complement receptor of myelomonocytic cells. A histological examination of the livers of control mice showed that the accumulation of neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
143
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(149 citation statements)
references
References 12 publications
6
143
0
Order By: Relevance
“…Experimental murine listeriosis is instrumental in elucidating host defense mechanisms against intracellular bacteria. Cells of the innate immune system play a pivotal role as a first line of defense against L. monocytogenes [2][3][4][5] and among these, Gr-1 1 cells are central for the elimination of this pathogen at early stages of infection [6][7][8]. Numerous cytokines such as GM-CSF, IL-3, IL-6, IL-11, and SCF promote granulopoiesis by themselves and/or in concert with G-CSF [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental murine listeriosis is instrumental in elucidating host defense mechanisms against intracellular bacteria. Cells of the innate immune system play a pivotal role as a first line of defense against L. monocytogenes [2][3][4][5] and among these, Gr-1 1 cells are central for the elimination of this pathogen at early stages of infection [6][7][8]. Numerous cytokines such as GM-CSF, IL-3, IL-6, IL-11, and SCF promote granulopoiesis by themselves and/or in concert with G-CSF [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore determined whether amelioration of listeriosis by a-GalCer treatment was caused by accelerated infiltration of inflammatory cells into the liver. Because Gr-1 1 cells serve as a first line of defense against L. monocytogenes infection, in particular in the liver [6][7][8]66, 67], we compared numbers of Gr-1 1 cells in the liver before and after a-GalCer treatment. Because CD11b surface expression is up-regulated on Gr-1 1 cells after activation [68], CD11b expression was analyzed, as well.…”
mentioning
confidence: 99%
“…Its ability to invade and multiply in a wide range of mammalian cells (Vazquez-Boland et al, 2001) is essential for development of systemic listeriosis. For example, the ability of L. monocytogenes to invade nonphagocytic cells plays an important role in this organism's traversal of the intestinal barrier (Lecuit et al, 2001;MacDonald & Carter, 1980;Racz et al, 1972), and its ability to multiply in hepatocytes is essential for causing a systemic infection (Conlan & North, 1991;Gaillard et al, 1996). Several bacterial factors that mediate internalization events have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…During systemic infection of mice with L. monocytogenes, the liver serves as a major site of bacterial replication (17)(18)(19)(20). Western blot analysis indicated that the mouse liver expresses Tuba (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to more directly test the hypothesis that the inlC.K173A mutant is compromised for spreading in the liver, we performed histological analysis. L. monocytogenes is known to produce foci in the liver that result from infection of hepatocytes (17,18,20). The size of these foci may reflect the efficiency of bacterial spreading.…”
Section: Resultsmentioning
confidence: 99%